Answer:
A=-3/2
B=3
c=3/2
a=-2
Explanation:
Knowing that for
,
when t<0 and using the definition of charge
![q(t)=\int_(-\infty)^0i(t')dt'+\int_0^t i(t')dt'=0+\int_0^t i(t')dt'](https://img.qammunity.org/2020/formulas/mathematics/college/oneuxytr1f2yoaxhn69xqpo34cemrjv8df.png)
The first term corresponds to q(0), the charge accumulated before t=0, in this case it luckily gives zero so we don't have to worry about it.
Let's proceed and integrate
then when t>0
![i(t)=3\int_0^t \left[ \int_0^tdt'-\inte_0^t e^(-2t')dt' \right]dt'=3\left[ t+(1)/(2)\left( e^(-2t)-1 \right) \right]=3t+(3)/(2)e^(-2t)-(3)/(2)\,\, C](https://img.qammunity.org/2020/formulas/mathematics/college/qtr63kvnsc6mydlce0iogv8jhjz6wrm9qf.png)
It is clear that:
A=-3/2
B=3
c=3/2
a=-2